ANALISIS AKUNTANSI PERTANGGUNGJAWABAN PADA PT. KELOLA JASA ARTHA SUB BRANCH PAREPARE - Arland (Journal AK-99, 2021)
This research aims to determinethe role of accountability accounting in the assessment of the performance of accountability centers in PT.Manage Artha Sub Branch Parepare Services. To obtain the results of this research, several variables are examined, namely the assessment of accountability centers and accountability accounting. This research uses qualitative methods in the form of data expressed in the form of sentences or descriptions. The data collection methods used in this study are interviews and documentation. The analysis used in this study to find out accountability accounting plays a role in assessing the centers of accountability i.e. qualitative descriptive methods. From the results of research on PT. Manage Artha Sub Branch Parepare Services, have not implemented accountability accounting well enough, this can be known with some conditions and characteristics that have not been met and the performance achieved is still not effective because it is stillabove budget.